If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y(y + 3)(y + -7) = 0 Reorder the terms: 4y(3 + y)(y + -7) = 0 Reorder the terms: 4y(3 + y)(-7 + y) = 0 Multiply (3 + y) * (-7 + y) 4y(3(-7 + y) + y(-7 + y)) = 0 4y((-7 * 3 + y * 3) + y(-7 + y)) = 0 4y((-21 + 3y) + y(-7 + y)) = 0 4y(-21 + 3y + (-7 * y + y * y)) = 0 4y(-21 + 3y + (-7y + y2)) = 0 Combine like terms: 3y + -7y = -4y 4y(-21 + -4y + y2) = 0 (-21 * 4y + -4y * 4y + y2 * 4y) = 0 (-84y + -16y2 + 4y3) = 0 Solving -84y + -16y2 + 4y3 = 0 Solving for variable 'y'. Factor out the Greatest Common Factor (GCF), '4y'. 4y(-21 + -4y + y2) = 0 Factor a trinomial. 4y((-3 + -1y)(7 + -1y)) = 0 Ignore the factor 4.Subproblem 1
Set the factor 'y' equal to zero and attempt to solve: Simplifying y = 0 Solving y = 0 Move all terms containing y to the left, all other terms to the right. Simplifying y = 0Subproblem 2
Set the factor '(-3 + -1y)' equal to zero and attempt to solve: Simplifying -3 + -1y = 0 Solving -3 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1y = 0 + 3 -1y = 0 + 3 Combine like terms: 0 + 3 = 3 -1y = 3 Divide each side by '-1'. y = -3 Simplifying y = -3Subproblem 3
Set the factor '(7 + -1y)' equal to zero and attempt to solve: Simplifying 7 + -1y = 0 Solving 7 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1y = 0 + -7 -1y = 0 + -7 Combine like terms: 0 + -7 = -7 -1y = -7 Divide each side by '-1'. y = 7 Simplifying y = 7Solution
y = {0, -3, 7}
| 7n(54)-9n=18 | | (8+z)(3z-4)=0 | | 5+4y=100 | | 4(y+3)(-y-8)=0 | | (2w+7)(5+w)=0 | | -16t^2+20t+8=0 | | (u+4)(u-1)=0 | | W^2+18w+c= | | (4x-36)+(2x+12)=180 | | (5+z)(3z-1)=0 | | x^4-2x^2=-20 | | 2w(w+7)(w-1)=0 | | 7x^2-4y=0 | | 10x^2+5x=50 | | m(5-x)=3-yforx | | 4r^2+4r=33 | | 24-5y+-7=189 | | -6(w-6)=3w+9 | | -2(2x+3)+8x=6(x-1)+3x | | 8-6x=3-7x | | 10=2h | | 28.50+8.75w=104.75+6.50w | | 9Y-81x=108 | | 6q+3q-q=24findq | | 90x+x=90 | | 8x+4y=10y | | 6x-2=-4c+8x | | 180x+x=180 | | 2(2-x)=8-2(2-x) | | f(x)=(15x) | | y+16=20 | | 90x+x=180 |